Faktor-Faktor Yang Mempengaruhi Cash Holding Pada Perusahaan Manufaktur Tahun 2016-2018 - Yosua Hansen Putra, Tony Sudirgo (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to determine whether there is a significant effect between profitability, leverage, net working capital, and growth opportunity on cash holding. This study uses 534 data of manufacturing companies that have been listed on the Indonesia Stock Exchange in the period of 2016-2018 using purposive sampling technique. By analyzing descriptive statistical data and using the Eviews 9.0 program. The results of this study indicate that profitability, leverage, net working capital, and growth opportunity have a positive and significant effect on cash holding.